2002
DOI: 10.1046/j.1532-5415.2002.50259.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment, Depressive Symptoms, and Functional Decline in Older People

Abstract: OBJECTIVES-Although cognitive impairment and depressive symptoms are associated with functional decline, it is not understood how these risk factors act together to affect the risk of functional decline. The purpose of this study is to determine the relative contributions of cognitive impairment and depressive symptoms on decline in activity of daily living (ADL) function over 2 years in an older cohort. DESIGN-Prospective cohort study.SETTING-A U.S. national prospective cohort study of older people, Asset and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
4
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(162 citation statements)
references
References 34 publications
10
141
4
7
Order By: Relevance
“…A previous study reported that disability and cognitive impairment exhibited a similar pattern of increasing frequency with age (Alonso Serra et al 1995), and subjects with low cognitive performance were at higher risk of functional impairment in subsequent years (Barberger-Gateau and Fabrigoule 1997). Another study also indicated that cognitive impairment is a risk factor for additional functional decline among patients with or without ADL dependence at baseline (Mehta et al 2002). Because there is an interaction between functional decline and cognitive impairment, further prospective studies would improve our understanding of specifically how cognitive impairment is related to the progression of functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that disability and cognitive impairment exhibited a similar pattern of increasing frequency with age (Alonso Serra et al 1995), and subjects with low cognitive performance were at higher risk of functional impairment in subsequent years (Barberger-Gateau and Fabrigoule 1997). Another study also indicated that cognitive impairment is a risk factor for additional functional decline among patients with or without ADL dependence at baseline (Mehta et al 2002). Because there is an interaction between functional decline and cognitive impairment, further prospective studies would improve our understanding of specifically how cognitive impairment is related to the progression of functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships persisted even after adjusting for baseline cognitive level and there was no significant interaction between cognitive impairment and depression in our study. Mehta et al (Mehta et al, 2002) found that in elderly people without ADL limitations, but not in those with ADL limitations at baseline, cognitive impairment and DS were both risk factors for functional decline. In a sample of vulnerable elders eligible for nursing home care, Li et al (Li and Conwell, 2009) found that cognitive decline was associated with more elevated IADL scores when depression status worsened, but this was not observed for ADL scores.…”
Section: Mechanisms Potentially Involved In the Association Between Dmentioning
confidence: 99%
“…Depression severity, for example, has been fairly consistently linked to functional disability (Lenze et al, 2005;van Gool et al, 2005;Stein et al, 2006). Depression can have direct effects on both cognitive function (Rosenstein, 1998) and functional status (Espiritu et al, 2001;Mehta et al, 2002;De Ronchi et al, 2005) leading to 'excess disability ' (i.e. disability beyond what may be expected based on level of cognitive functioning alone).…”
Section: Introductionmentioning
confidence: 99%